Using problem-based learning during student placements to embed theory in practice - Sadlo, Gaynor (International Journal of Practice-based Learning in Health and Social Care, 2016)
Practice placements, a prominent part of the education of health and social care professionals, are strongly validated by theories of adult learning. Being situated in authentic workplaces in contact with people in need, motivation to learn is strong. However, it is not always easy for students to realise the knowledge that practitioners are using in the setting, as it becomes tacit. Problem-based learning (PBL) is a form of student-centred university teaching deliberately structured to support development of students’ theoretical understanding, critical thinking, professional reasoning and team skills. PBL is recognised world-wide for its applicability to health and social science curricula, but to date its potential as a method to activate theoretical learning during placements has not been realised. The aim of this masterclass is to inspire and encourage placement educators and students to use PBL as an effective, enjoyable way to structure knowledge development during placement. The outcomes of this paper include appreciation of the rationale and stages of the PBL cycle in a practice environment, and sufficient understanding about how PBL can be used to embed theory in practice to give it a try. Case studies and supervision sessions need to be adjusted a little to explicitly include a self-directed learning stage to develop students’ knowledge, illustrated here through a case example. Students identify their own learning needs to guide their independent learning, maximising use of placement time. PBL in practice settings is a flexible approach, applicable to one-to-one situations, with pairs, groups (including inter-professional), and within work-based learning for staff development.